Piloting Scenarios for Children with Autism to Learn About Visual Perspective Taking - Wood, Luke Jai; Robins, Ben; Lakatos, Gabriella; Syrdal, Dag Sverre; Zaraki, Abolfazl; Dautenhahn, Kerstin (Towards Autonomous Robotic Systems, 2018)
Visual Perspective Taking (VPT) is the ability to see the world from another person’s perspective, taking into account what they see and how they see it, drawing upon both spatial and social information. Children with autism often find it difficult to understand that other people might have perspectives, viewpoints, beliefs and knowledge that are different from their own which is a fundamental aspect VPT. In this paper, we present the piloting of scenarios for our first large scale pilot-study using a humanoid robot to assist children with autism develop their VPT skills. The games were implemented with the Kaspar robot and to our knowledge this is the first attempt to improve the VPT skills of children with autism through playing and interacting with a humanoid robot.